1984
DOI: 10.1136/oem.41.4.533
|View full text |Cite
|
Sign up to set email alerts
|

n-Hexane metabolism in occupationally exposed workers.

Abstract: ABSTRACr Lung uptake and excretion of n-hexane were studied in ten workers in a shoe factory. Simultaneous samples of inhaled and alveolar air were collected with the aid of a Rhan-Otis valve, personal samplers, and charcoal tubes. Alveolar excretion was monitored during a six hour postexposure period. Uptake was calculated from lung ventilation, the retention coefficient, and environmental concentrations. The amount of exhaled n-hexane was calculated from the decay curve. According to the experimental data, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…With greatly fluctuating exposure concentrations (45 -405 ppm n-hexane) an average retention rate of 15 % was determined for workers of a shoe factory (10). This value was confirmed by further investigations (46,82). After the end of exposure a large amount of the n-hexane at first retained is exhaled again unchanged (50).…”
supporting
confidence: 59%
“…With greatly fluctuating exposure concentrations (45 -405 ppm n-hexane) an average retention rate of 15 % was determined for workers of a shoe factory (10). This value was confirmed by further investigations (46,82). After the end of exposure a large amount of the n-hexane at first retained is exhaled again unchanged (50).…”
supporting
confidence: 59%
“…As urinary samples were taken approximately 16 hr after the end of last shift (17:00) and the half-life of urinary excretion of HD is 13-14 hr (IPCS, 1991), HD in end-of-shift urine of workers was estimated to be at least twice that in the samples examined, i.e., about 0.8-6 (mean, 2.4) mg/g Cn. These values may correspond to 13-100 (mean 40) ppm of n-hexane in air during work, as it has been reported that 3 mg/g Cn of HD in end-ofshift urine is equivalent to 50 ppm of n-hexane in air (Mutti et al, 1984).…”
Section: Subjectsmentioning
confidence: 95%
“…HD in end-of-shift urine of workers was estimated to be at least twice that in the samples examined, i.e., about 0.8-6 (mean 2.4) mg/g Cn, as urinary samples were taken approximately 16 hr after the end of last shift (17:00) and the half-life of urinary excretion of HD is 13-14 hr 31) . These values may correspond to 13-100 (mean 40) ppm of n-hexane in air during work, as it has been reported that 3 mg/g Cn of HD in end-of-shift urine is equivalent to 50 ppm of n-hexane in air 32) . Similarly, MHA concentrations in urine of the workers at the end of shift were estimated at approximately 5-19 folds of those in the morning urine, i.e.…”
Section: Subjectsmentioning
confidence: 99%